Return to play after symptomatic lumbar disc herniation in elite athletes: A systematic review and meta-analysis of operative versus nonoperative treatment - Sedrak, P.; Shahbaz, M.; Gohal, C. (Sports Health: A Multidisciplinary Approach, 2021)
Context: The prevalence of symptomatic lumbar disc herniation (LDH) in athletes can be as high as 75%. For elite athletes diagnosed with LDH, return to play (RTP) is a major concern, and thus comparing surgical with nonoperative care is essential to guide practitioners and athletes, not just in terms of recovery rates but also speed of recovery. Objective: The purpose of this systematic review is to provide an update on RTP outcomes for elite athletes after lumbar discectomy versus nonoperative treatment of LDHs. Data Sources: A search of the literature was conducted using 3 online databases (MEDLINE, EMBASE, and PubMed) to identify pertinent studies. Study Selection: Yielded studies were screened according to the inclusion criteria. Study Design: Systematic review with meta-analysis. Level of Evidence: Level 4. Data Extraction: Relevant data were extracted. A meta-analysis was performed comparing RTP rate for all comparative studies. Results: Twenty studies met the inclusion criteria and were included in this review. Overall, 663 out of 799 patients (83.0%) returned to play in the surgical group and 251 out of 308 patients (81.5%) returned to play in the nonoperative group. No statistically significant difference for RTP rate was found (odds ratio, 1.39; 95% CI, 0.58-3.34; P = 0.46; I2, 71%). The mean time to RTP for patients undergoing lubar discectomy was 5.19 months (range 1.00-8.70 months), and 4.11 months (range 3.60-5.70 months) for those treated conservatively. Conclusion: There was no significant difference in RTP rate between athletes treated with operative or nonoperative management of LDHs, nor did operative management have a faster time to RTP. Athletes should consider the lack of difference in RTP rate in addition to the potential risks associated with spinal surgery when choosing a treatment option. Future randomized controlled trials are needed on this topic to allow for high-powered conclusions.